Active video gaming improves body coordination in survivors of childhood brain tumours. Issue 21 (8th October 2016) - Sabel, Magnus; Sjölund, Anette; Broeren, Jürgen; Arvidsson, Daniel; Saury, Jean-Michel; Blomgren, Klas; Lannering, Birgitta; Emanuelson, Ingrid
Abstract: Purpose: We investigated whether active video gaming (AVG) could bring about regular, enjoyable, physical exercise in children treated for brain tumours, what level of physical activity could be reached and if the children's physical functioning improved. Methods: Thirteen children, aged 7–17 years, were randomised to either AVG or waiting-list. After 10–12 weeks they crossed-over. Weekly Internet coaching sessions were used to sustain motivation and evaluate enjoyment. Energy expenditure (EE) levels were measured as Metabolic Equivalent of Task (MET), using a multisensory activity monitor. Single-blinded assessments of physical functioning were done, using the Bruininks–Osteretsky Test of Motor Performance, second edition, evaluating participants before and after the intervention period, as well as comparing the randomisation groups after the first period. Results: All patients completed the study. AVG sessions (mean duration 47 minutes) were performed on 72% of all days. Mean EE level during AVG sessions was 3.0 MET, corresponding to moderate physical activity. The Body Coordination score improved by 15% ( p = 0.021) over the intervention period. Conclusions: In this group of childhood brain tumour survivors, home-based AVG, supported by a coach, was a feasible, enjoyable and moderately intense form of exercise that improved Body Coordination. Implications for Rehabilitation: Childhood brain tumour survivors frequently have cognitive problems, inferior physical functioning and are less physically active compared to their healthy peers. Active video gaming (AVG), supported by Internet coaching, is a feasible home-based intervention in children treated for brain tumours, promoting enjoyable, regular physical exercise of moderate intensity. In this pilot study, AVG with Nintendo Wii improved Body Coordination.